FORMULATION, OPTIMIZATION, AND IN VITRO EVALUATION OF POLYMERIC NANOSUSPENSION OF FLURBIPROFEN - PANKAJ JADHAV; ADHIKRAO YADAV (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: At present, more than 40% of drugs are poorly water-soluble that leads to reduced bioavailability. The objective of the present investigation was to overcome the issue of poor aqueous solubility of drug; therefore, stable flurbiprofen (FBF) nanosuspensions were developed by nanoprecipitation method. Materials and Methods: Based on particle size, zeta potential, and entrapment efficiency, the polymeric system of hydroxypropyl methylcellulose E15 and poloxamer 188 was used effectively. The prepared formulations were evaluated for Fourier transform infrared spectroscopy, transmission electron microscopy, differential scanning calorimetry, powder X-ray diffraction, saturation solubility, entrapment efficiency, particle size, zeta potential, dissolution profile, and stability. Results: The resultant FBF nanosuspensions depicted particles in size range of 200–400 nm and were physically stable. After nanonization, the crystallinity of FBF was slightly reduced in the presence of excipients. The aqueous solubility and dissolution rate of all FBF nanosuspensions were significantly increased as compared with FBF powder. Conclusion: This investigation demonstrated that nanoprecipitation is a promising method to develop stable polymeric nanosuspension of FBF with significant increase in its aqueous solubility.